2020
DOI: 10.1155/2020/1416945
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics Analysis of Myocardial Metabolic Dysfunction in Patients with Cardiac Natriuretic Peptide Resistance

Abstract: Brain natriuretic peptide (BNP) is an important biological marker and regulator of cardiac function. BNP resistance is characterized by high concentrations of less functionally effective BNP and common in heart failure (HF) patients. However, the roles and consequences of BNP resistance remain poorly understood. Investigate the effects of cardiac BNP resistance and identify potential metabolic biomarkers for screening and diagnosis. Thirty patients and thirty healthy subjects were enrolled in this study. Cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In fact, 9 of the top 10 terms are associated with the metabolic process which is in good agreement with our past findings that NPs may play a pivotal role in metabolic functions. [27][28][29] Bubble plots show these metabolic processes in BP bars, the bubble size shows the counts of genes, the number of enriched genes are listed in brackets on the left, and the color of the bubble represents the P-value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, 9 of the top 10 terms are associated with the metabolic process which is in good agreement with our past findings that NPs may play a pivotal role in metabolic functions. [27][28][29] Bubble plots show these metabolic processes in BP bars, the bubble size shows the counts of genes, the number of enriched genes are listed in brackets on the left, and the color of the bubble represents the P-value.…”
Section: Resultsmentioning
confidence: 99%
“…47 More importantly, we are highly concerned with the possible functional roles of NPRA and BNP resistance in the regulation of cardiac metabolism. 28,29 BNP resistance is characterized by high concentrations of less functionally effective BNP and is common in heart failure (HF) patients. Our previous result showed that NPRA-deficient mice have distinct metabolic patterns compared with control mice but the molecular mechanism that could account for this observation remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical literature includes multiple studies associating metabolites with HF characteristics and outcomes. Examples include findings that metabolic profiling can discriminate and identify patients at risk of HF-related decompensation, and metabolomic profiles showing differentially expressed signaling pathways are associated with lower cyclic guanosine monophosphate/brain natriuretic peptide (cGMP/BNP) ratios in HF patients [77,78]. Of relevance to the diet and gut health relationship, the gut-related metabolite trimethylamine N-oxide (TMAO) is associated with acute and long-term adverse outcomes in HF [79].…”
Section: Metabolic and Metabolomic Biomarkersmentioning
confidence: 99%